Rivers and Floodplains as Key Components of Global Terrestrial Water Storage Variability. Issue 20 (21st October 2017) - Getirana, Augusto; Kumar, Sujay; Girotto, Manuela; Rodell, Matthew
Abstract: This study quantifies the contribution of rivers and floodplains to terrestrial water storage (TWS) variability. We use state‐of‐the‐art models to simulate land surface processes and river dynamics and to separate TWS into its main components. Based on a proposed impact index, we show that surface water storage (SWS) contributes 8% of TWS variability globally, but that contribution differs widely among climate zones. Changes in SWS are a principal component of TWS variability in the tropics, where major rivers flow over arid regions and at high latitudes. SWS accounts for ~22–27% of TWS variability in both the Amazon and Nile Basins. Changes in SWS are negligible in the Western U.S., Northern Africa, Middle East, and central Asia. Based on comparisons with Gravity Recovery and Climate Experiment‐based TWS, we conclude that accounting for SWS improves simulated TWS in most of South America, Africa, and Southern Asia, confirming that SWS is a key component of TWS variability. Key Points: SWS contributes to TWS primarily in the tropics and in major rivers flowing over arid regions or at high latitudes SWS has low impact in Western U.S., Northern Africa, Middle East and central Asia, and most of Australia Rivers and floodplains store 2, 400 km3 with an annual variability of 2, 700 km3, contributing to 7% of TWS change globally